Evaluate: (-a)(b)(-a + b) if a= 6 and b= -3

Question

Evaluate:
(-a)(b)(-a + b) if a= 6 and b= -3

in progress 0
Eliza 2 weeks 2021-10-10T23:10:47+00:00 1 Answer 0

Answers ( )

    0
    2021-10-10T23:12:34+00:00

    There are two ways to solve this question.

    1) To solve this question, we need to substitute a = 6 and b = -3 into the given expression and then evaluate:

    (-a)(b)(-a + b)

    = (-6)(-3)(-6 + (-3))

    = 18(-9)

    = -162

    2) An alternative method is to simplify (-a)(b)(-a + b) into an expression without brackets and then substitute a = 6 and b = -3:

    1. (-a)(b)(-a + b)

    = (-ab)(-a + b)

    = -ab*(-a) + (-ab)*b

    = a^(2)b+ (-ab^(2))

    = a^(2)b – ab^(2)

    2. a^(2)b – ab^(2)

    = 6^(2)*(-3) – 6*(-3)^2

    = 36*(-3) – 6*9

    = -108 – 54

    = -162

    The key to either method is to be careful with placement of brackets, especially where there are negative values involved.

Leave an answer

Browse
Browse

27:3+15-4x7+3-1=? ( )